Performance measure in a probabilistic re-entrant stress testing line - Kumar, , S; Omar, , MK (2005)
This paper presents a modified approximation model based on mean value analysis (MVA) technique and virtual lot clustering method for a probabilistic re-entrant stress testing line. The objective is to determine the total cycle time and the mean throughput rate of the Power Shock Stress Testing (PSST) process for a given number of lots. Using the analytical and simulation method, we analyse a five-stage queuing system with re-entrant lines into the second stage under various probabilistic routing condition and comparison results are made. The model can be used by operation managers to predict their lots cycle times.